The Effect of Gender on Sprint Performance of 10-13 Aged Middle School Students - Serhat Turan; Hacı Mustafa Akgül (ümit doğan üstün, 2016)
The aim of the study was to investigate the effect of gender on the 30 m sprint performance of middle school students (10-13 ages). The study included 25 male and 25 female total 50 middle school students. The mean age of female students was found as 12,36 ± 0,48 (year), the mean body weight as 42,03 ± 3,63 (kg), and the mean height as 151,11 ±5,61 (cm), and the mean age of male students was found as 12,28 ± 0,45 (year), the mean height as 152,28 ± 5,04 (cm), and the mean body weight as 43,35 ± 1,88 (kg). The mean sprint performance of female students was calculated as 6,33 ± 0,53 seconds, and the mean sprint performance of the male students was 6,17 ± 0,47 seconds. As a result the effect of gender on sprint performance was found to be insignificant between the groups (p>0,05).